A note on Antarctic benthic mollusks collected with a beam-trawl from Breid Bay by the 25th Japanese Antarctic Research Expedition - Okutani, Takashi (Kokuritsu Kyokuchi Kenkyūsho (Tokio), 1986)
The molluscan specimens sorted out from benthos samples trawled from depths of 31O and 215m in Breid Bay were studied. A single species of Polyplacephora, 7 gastropods, one scaphopod, 6 bivales and 2 octopod cephalopods were identified. The general compositions of the present cotlection represents typical shelf fauna in the Antarctic